Growth and reproduction of the shrimp Rimapenaeus constrictus (Decapoda: Penaeidae) from the southeastern coast of Brazil - Garcia, Joyce Rocha [UNESP]; Wolf, Milena Regina [UNESP]; Da Costa, Rogerio Caetano [UNESP]; Castilho, Antonio Leaõ [UNESP] (Elsevier, 2016)
Few studies have been performed on the shrimp Rimapenaeus constrictus, despite its wide geographic distribution in the western Atlantic Ocean. The population dynamics of R. constrictus were evaluated, focusing on sex ratios, growth, longevity, and reproduction, in the Cananeia region, along the southern coast of Saõ Paulo state, Brazil. Monthly trawls were conducted from July 2012 through May 2014 using a shrimp boat outfitted with double-rig nets. The shrimp were identified according to their sex and reproductive condition, and carapace length (CL) was measured. A total of 1702 individuals were collected, and females were found to reach sexual maturity at a greater CL (9 mm) than males (7 mm). Based on the estimated growth curve parameters, males exhibit shorter longevity (0.73 years) than females (1.14 years). In terms of the sex ratio, there was a statistically significant bias toward females observed over the months, beginning at a CL of 9 mm (binomial test, p<0.05). The seasonal reproductive pattern recorded during the spring and summer coincided with higher temperatures and chlorophyll concentrations (plankton production), which suggests that food availability for protozoeal and mysis larvae may be an important selective factor in the reproductive success of R. constrictus.
Keywords: Match-mismatch theory; Roughneck-shrimp; Seasonality; Subtropical region